Brain Delivery Strategies for Biomacromolecular Drugs: Intranasal Administration - Wu H; Li C; Yuan H; Zhao J; Li S (International Journal of Nanomedicine, 2025)
Huanhuan Wu,1,2,* Chenyu Li,1,2,* Hong Yuan,3 Jingyuan Zhao,3,* Shuai Li1 1The First Affiliated Hospital of Dalian Medical University, Dalian, People’s Republic of China; 2Dalian Medical University, Dalian, People’s Republic of China; 3Central Hospital of Dalian University of Technology, Dalian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hong Yuan, Central Hospital of Dalian University of Technology, Clinical Laboratory Center, Dalian, People’s Republic of China, Email yuanhonglab@163.com Shuai Li, The First Affiliated Hospital of Dalian Medical University, Department of Pharmacy, Dalian, People’s Republic of China, Email shuaili2015@outlook.comAbstract: Macromolecular Drugs (including monoclonal antibodies, recombinant proteins, and nucleic acid therapies) have become a cornerstone strategy for intervening in complex pathological mechanisms such as cancer, autoimmune diseases, and genetic disorders due to their high specificity for disease targets and low off-target toxicity. However, compared to traditional small-molecule drugs, the high molecular weight (> 10 kDa) and structural complexity of macromolecular drugs result in extremely low transmembrane permeability. This is particularly challenging in the treatment of central nervous system (CNS) diseases, where the blood-brain barrier (BBB) imposes stringent selectivity, further limiting drug delivery efficiency. This review focuses on the breakthrough strategy of nose-to-brain (NtB) drug delivery. On one hand, the NtB pathway bypasses the BBB, enabling direct CNS drug delivery. On the other hand, nanocarrier technology can synergistically achieve systemic delivery and brain-targeted transport. Based on the latest research advances, this article systematically examines the feasibility of delivering macromolecular drugs via NtB administration. We comprehensively summarize relevant delivery carriers and discuss the potential advantages of intranasal-brain delivery for CNS disease treatment. Notably, while significant progress has been made in this field, further exploration is still needed regarding the mechanisms of NtB delivery and challenges in clinical translation. Keywords: macromolecular drugs, BBB, central nervous system disorders, nanocarriers, intranasal administration